Associations of body condition score, body condition score change, and hyperketonemia with mastitis, reproduction, and milk production - K.C. Krogstad; B.J. Bradford (Journal of Dairy Science)
ABSTRACT: Body condition score and hyperketonemia (HYK) have been associated with diseases, fertility, and culling, but data are contradictory about their association with pregnancy loss. Our objective was to conduct a retrospective cohort study to investigate associations between BCS, BCS change (ΔBCS), blood BHB, and HYK with mastitis, pregnancy per artificial insemination (P/AI), pregnancy loss (PGL), milk yield, and risk of leaving the herd on a Michigan dairy farm that uses an automated milking system (AMS). We recorded BCS for cows prepartum (14 d before calving) and postpartum (14–21 DIM), and multiparous cows were evaluated for HYK between 3 and 7 DIM. Records were gathered from herd management software. Univariable associations of BCS (prepartum n = 826, postpartum n = 956) ΔBCS (n = 819), and BHB (n = 628) with mastitis, P/AI, PGL, and risk of leaving the herd were evaluated. Survival analyses investigated the association of BCS, ΔBCS, and HYK within parity with mastitis, pregnancy, and hazard of leaving the herd during lactation. We examined the association of BCS, ΔBCS, and HYK with whole lactation milk yield using repeated-measures mixed models. Thinner cows both pre- (BCS < 3.25) and postpartum (BCS < 2.75) had greater risk of leaving the herd (odds ratio [OR] = 1.48 and 2.16, respectively) compared with their moderate BCS herd mates. Cows who lost ≥0.375 units of BCS after calving had greater risk of PGL (OR = 4.99). Cows that lost ≥0.75 units of BCS had greater risk of being culled (OR = 1.80). Cows with HYK were at greater risk of mastitis (risk ratio = 1.34) and being culled (OR = 2.27). Cows with increasing BHB had greater risk of PGL and being culled such that a 1 mmol/L increase in BHB resulted in 2.32 and 1.67 greater risk, respectively. Hyperketonemic cows within third+ parity made 5.4 kg/d ± 1.04 kg/d (difference ± standard error of difference) less milk yield over their lactation compared with non-HYK third+ parity cows. Our data support previous findings that BHB and HYK had adverse associations with mastitis, fertility, leaving the herd, and milk yield. Our data also suggest that BCS loss after calving and BHB during wk 1 of lactation are risk factors associated with incidence of PGL.